A novel, rapid, ultrasensitive diagnosis platform for detecting Candida albicans using restriction endonuclease‐mediated real-time loop-mediated isothermal amplification - Wang, Yizhe; Zhou, Yuhong; Lu, Jingrun; Yu, Honglan (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionCandida albicans (C. albicans, CA) is an essential invasive fungus in clinical diagnosis. Although several detection methods exist, none meet the need for early diagnosis. A rapid, sensitive, and specific diagnostic tool is crucial for effective prevention and control of C. albicans infections.MethodsThis study aimed to develop a new, rapid, and ultrasensitive diagnostic tool for C. albicans detection based on restriction endonuclease-mediated real-time loop-mediated isothermal amplification (ERT-LAMP-CA). The ERT-LAMP-CA technology combines LAMP amplification, restriction endonuclease cleavage, and real-time fluorescence detection in a single reaction tube, which can complete a diagnosis of C. albicans in a short time (approximately 1 h).ResultsHerein, we developed the primer sequences required for ERT-LAMP-CA based on the ITS2 gene of C. albicans and found that ERT-LAMP-CA limit of detection was approximately 500 ag/μL genomic DNA and can present negative results for non-C. albicans templates. We tested sputum samples from 64 patients with suspected C. albicans infections to validate ERT-LAMP-CA applicability in clinical sample testing and found that ERT-LAMP-CA was consistent with multiplex PCR-capillary electrophoresis.DiscussionIn conclusion, ERT-LAMP-CA is a rapid, accurate, and sensitive assay with excellent potential for clinical and basic laboratory diagnosis and an efficient screening strategy.